2010
DOI: 10.1016/j.foodcont.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR-based detection and quantification of genetically modified maize in processed feeds commercialised in Malaysia

Abstract: a b s t r a c tThe present study which dealt mainly with processed feeds and some maize samples sold commercially in Malaysia evaluated the implementation of a real-time PCR cycling system for singleplex screening of eight target sequences (lectin, hmg, adh1, p35S, NK603, GA21, MON810 and MON863) and quantification of four genetically modified (GM) maize events (NK603, GA21, MON810 and MON863). The effects of using proprietary glass magnetic particles to bind DNA to their surface were also investigated in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…[20] However, the purity of obtained DNA can be significantly affected by degree of processing, extraction procedure and different components of sample matrix. [1] Therefore, to reduce the false negative results quality confirmation of genomic DNA for all samples and CRMs were carried out by agarose gel electrophoresis. [21,22] It was observed that the specific lectin and invertase endogenous genes are available for further investigation of GM sequences from soy and maize, respectively (Figure 2).…”
Section: Quality Assurancementioning
confidence: 99%
See 2 more Smart Citations
“…[20] However, the purity of obtained DNA can be significantly affected by degree of processing, extraction procedure and different components of sample matrix. [1] Therefore, to reduce the false negative results quality confirmation of genomic DNA for all samples and CRMs were carried out by agarose gel electrophoresis. [21,22] It was observed that the specific lectin and invertase endogenous genes are available for further investigation of GM sequences from soy and maize, respectively (Figure 2).…”
Section: Quality Assurancementioning
confidence: 99%
“…[13] The observation of maize food products was consistent with the study conducted in Malaysia which have indicated that of all 20 non-labeled maize samples tested, 13 (65%) were determined to be positive for GM materials. [1] GMO screening study in Kingdom of Saudi Arabia indicated that out of 64 maize containing products, 28 were positive for CaMV 35 S or NOS terminator. [27] In the other study, Gürakan and Aydın (2011), examined 31 maize sold samples for GMO detection by targeting screening materials.…”
Section: Quality Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…However, consumers and environmental groups, have questioned whether the extent of testing is sufficient [3]. The controversy surrounding GMO crops has left consumers uncertain about the issue [4]. Fears for the safety of the consumption of foods made from GMO crops are also due that at the beginning the preparation of transgenic plants involves the bacterium Agrobacterium tumefacient using the Ti plasmid as a gene transfer vector.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of countries are actively pursuing detection and monitoring of GM products in food commodities. Some examples of those studies performed in various countries include reports from Malaysia, 24,25 Brazil, 26 China, 27 Saudi Arabia, 28 etc.…”
Section: Introductionmentioning
confidence: 99%